Girdling and type af cutting in rooting of jackfruit - Lederman, Ildo Eliezer; Bezerra, João Emmanoel Fernandes; Aschoff, Maria Nazareth Alves; Carvalheira, Rogério C.F. (Pesquisa Agropecuaria Brasileira, 2014)
A branch rooting experiment was carried out with jackfruit tree (Artocarpus heterophyllus Lam.) branches under intermittent mist, using a completely randomized block design with a factorial 3(2 x 2 x 3) arrangement. Two cutting types (terminal an subterminal, two girdling types (with and without girdling) and three hormone treatments (indolbutyric acid 5.000 ppm, naphthaleneacetic acid 2.000 ppm, and check) were used: The subterminal cutting proved to be superior to the terminal, and reached 17,8% of rooting when girdling was done. However, when branches were left ungirdled, neither terminal nor subterminal cutting took root. The use of indolbutyric and naphthaleneacetic acids did not improve rooting percentage.